New possibilities of pathogenetic therapy for allergic rhinitis - A. A. Krivopalov; S. A. Rebrova; L. I. Krivopalova (Медицинский совет, 2018)
Allergic rhinitis is one of the most common human diseases that affect patients’ quality of of life. There has been a significant increase in incidence rates related to allergic rhinitis in the Russian Federation and the world. Second-generation antihistamines having high H1-receptor affinity constitute the main pharmacological group for the treatment of allergic rhinitis. The article presents an overview of Bilastin as a novel drug of the above group.